Ethical Perception of Enactment of The Information and Electronic Transactions Act in Indonesia - Mia Angeline; Yuanita Safitri (Jurnal InterAct, 2016)
The ratification of the Indonesian Act of Information and Electronic Transactions (UU ITE) on 21st April 2008 is still causing controversies to this day. In 2014 there were a number of controversial cases related to “loopholes” in UU ITE alone. Among them are three cases to be discussed in this research, which occurred in social media. These cases are Benhan vs Misbakhun, Florence vs citizens of Yogyakarta, and the case of Bupati in East Kutai. Research questions addressed in this paper focused on regulatory and ethical perceptions of the above cases. This research used a qualitative approach with case study using in-depth interview and literature review, to understand behavior of social media users in relation of the cases as stated above.